Perlindungan Hukum terhadap Anak sebagai Korban Cybersex Trafficking di Aplikasi Live Streaming HOT51 - Putu Sherly Chandra Sasmitha; Ni Gusti Agung Ayu Mas Tri Wulandari; Ni Nyoman Juwita Arsawati; Putu Eva Ditayani Antari (Pusat Riset dan Inovasi Nasional, 2026)
The advancement of information technology has brought significant changes to society but also generated new crimes, such as online child sexual exploitation (cybersex trafficking). This study examines this phenomenon by focusing on the live streaming application